TANGENT AND NORMALS

PREVIOUS EAMCET BITS 1. The equation to the normal to the curve y 4 = ax 3 at (a, a) is 1) x + 2y = 3a 2) 3x − 4y + a = 0 3) 4x + 3y = 7a Ans: 3 dy 3ax 2 3a 3 3 ⎛ dy ⎞ Sol. y 4 = ax 3 ⇒ 4y3 = 3ax 2 ⇒ ⇒m=⎜ ⎟ = 3 = dx 4 4y3 ⎝ dx ⎠( a,a ) 4a [EAMCET 2008] 4) 4x − 3y = 0

2.

4 ( x − a ) ⇒ 4x + 3y = 7a 3 The length of the substangent at (2, 2) to the curve x5 = 2y4 is 1) 5/2 2) 8/5 3) 2/5 Ans: 2
Equation of the normal is y − a = −
4

[EAMCET 2008]

4) 5/8

dy dy 5x 4 5 ( 2 ) 5 Sol. x 5 = 2y 4 ⇒ 5x 4 = 8y3 ⇒ = 3 = = 3 dx dx 8y 4 8 ( 2) 2 2 8 = = m 5/ 4 5 3. The length of tangent, subtangent normal and subnormal for the curve y = x2 + x – 1 at (1, 1) are A, B, C and D respectively, then their increasing order is [EAMCET 2007] 1) B, D, A, C 2) B, A, C, D 3) A, B, C, D 4) B, A, D, C Ans:4 ⎛ dy ⎞ Sol. m = ⎜ ⎟ = 3 ⎝ dx ⎠(1,1) Length of the subtangent

10 3 1 B = length of subtangent = 3 C = length of normal = 10 D = length of subnormal = 3 ∴B<A<D<C 4. If θ is the angle between the curves xy = 2 and x 2 + 4y = 0 , then tanθ = 1) 1 2) – 1 3) 2 4) 3 Ans: 4 2 −x 2 y= Sol. y = , x 4 3 x = −8 ( −2, −1)

A = length of tangent =

[EAMCET 2006]

x = −2 y = −1 dy −2 −1 m1 = = = dx x 2 2

1

Tangent and Normals

m2 =

dy −2x − x = = =1 dx 4 2 −1 3 −1 m + m2 tan θ = 1 = 2 = 2 =3 1 1 1 + m1 m 2 1− 2 2

5.

Match the points on the curve 2y2 = x + 1 with the slopes of normals at those points and choose [EAMCET 2004] the correct answer. List –I List – II I) (7, 2) a) −4 2 ⎛ 1 ⎞ b) – 8 II) ⎜ 0, ⎟ 2⎠ ⎝ III) (1, –1) c) 4 IV) 3, 2 d) 0

(

)

1) b, d, c, a Ans: 2 Sol. 2y 2 = x + 1 ⇒ − −

2) b, e, c, a

e) −2 2 3) b, c, e, a

4) b, e, a, c

−dx = −4y = slope of the normal dy

dx at ( 7, 2 ) = −8 dy

dx ⎛ 1 ⎞ at 0, ⎟ = −2 2 dy ⎜ 2⎠ ⎝ dx − at (1, −1) = 4 ; dy dx − at 3, 2 = −4 2 dy

(

)

6.

The angle between the curves y = sin x and y = cos x is 1) tan
−1

(2 2 )

2) tan

−1

(3 2 )

3) tan

−1

(3 3 )

4) tan

−1

(5 2 )

[EAMCET 2003]

Ans: 1 Sol. y = sin x; y = cos x ⇒ x =

π 4

π 1 = 4 2 π −1 m 2 = − sin = 4 2 m1 = cos ⎛ m − m2 ⎞ −1 θ = tan −1 ⎜ 1 ⎟ = tan 2 2 ⎝ 1 + m1 m 2 ⎠

(

)
2

Tangent and Normals
The two curves x = y2, xy = a3 cut orthogonally at a point, then a2 = 1) 1/3 2) 1/2 3) 2 4) 3 Ans: 2 Sol. x = y 2 , xy = a 3 7.
2ym1 = 1 m 2 = 1 −a 3 ⇒ m1 = 2 2y x

[EAMCET 2002]

m1m 2 = −1 ⇒

1 a3 . = +1 2y x 2 xy 1 =1⇒ x = 2 2x y 2
3

3 1 1 ⎛1⎞ ⇒ (a2 ) = ⎜ ⎟ ∴ a2 = 2 8 ⎝2⎠ 8. The equation of the tangent to the curve 6y = 7 – x3 at (1, 1) is 1) 2x + y = 3 2) x + 2y = 3 3) x + y = - 1 Ans: 2 dy 1 at (1,1) = − Sol. 6y = 7 − x 3 ⇒ dx 2 −1 Equation of the tangent is y – 1 = ( x − 1) 2 ⇒ x + 2y − 3 = 0 9. The angle between the curves y2 =4x, x 2 = 4y at ( 4, 4 ) is

a 6 = x 2 y2 = x3 =

[EAMCET 2001] 4) x + y + 2 = 0

[EAMCET 2000]
4) π 4

⎛1⎞ ⎛3⎞ 1) tan −1 ⎜ ⎟ 2) tan −1 ⎜ ⎟ ⎝2⎠ ⎝4⎠ Ans: 2 dy 1 Sol. y 2 = 4x ⇒ at ( 4, 4 ) = = m1 dx 2 dy x 2 = 4y ⇒ at ( 4, 4 ) = 2 = m 2 dx m − m2 ⎛3⎞ T an θ = 1 ⇒ θ = tan −1 ⎜ ⎟ 1 + m1m 2 ⎝4⎠
10.

3)

π 2

Area of the triangle formed by the normal to the curve x = esin y at (1, 0 ) with the coordinate axes is

[EAMCET 2000]
1 4 Ans: 2 1) 2) 1 2 dy 1 = dx x cos y 3) 3 4 4) 1

Sol. x = esin y ⇒ log x = sin y ⇒

dy at (1, 0 ) = 1 = slope of the tangent dx ∴ Equation of the normal is x + y – 1 = 0 ∴ Area of the triangle with normal and coordinate axes = 1/ 2

3